THE WAYS OF USING PUN AND ZEUGMA IN ENGLISH POETRY - Saidova Iroda Anvar qizi (Journal of new century innovations, 2022)
Polysemy is a category of lexicology and as such belongs to language-as-a- system. In actual everyday speech polysemy vanishes unless it is deliberately retained for certain stylistic purposes. A context that does not seek to produce any particular stylistic effect generally materializes but one definite meaning. However, when a word begins to manifest an interplay between the primary and one of the derivative meanings we are again confronted with an SD. Let us analyse the following example from Sonnet 90 by Shakespeare1 where the key-words are intentionally made to reveal two or more meanings."Then hate me if thou wilt, if ever now. Now while the world is bent my deeds to cross."The word 'hate' materializes several meanings in this context. The primary meaning of the word, according to the Shorter Oxford English Dictionary, is 'to hold in very strong dislike'.